If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -3 = -3 + 4x Reorder the terms: -3 + 6x = -3 + 4x Add '3' to each side of the equation. -3 + 3 + 6x = -3 + 3 + 4x Combine like terms: -3 + 3 = 0 0 + 6x = -3 + 3 + 4x 6x = -3 + 3 + 4x Combine like terms: -3 + 3 = 0 6x = 0 + 4x 6x = 4x Solving 6x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6x + -4x = 4x + -4x Combine like terms: 6x + -4x = 2x 2x = 4x + -4x Combine like terms: 4x + -4x = 0 2x = 0 Divide each side by '2'. x = 0 Simplifying x = 0
| 3.7f=33 | | Y=0.6x+16 | | -3/6÷5/ | | C=20h+30 | | .75+d=4.5 | | -20-10k=-30 | | Y+.75=6 | | -8p-15=-p-4p | | 4.38=c-7.29 | | 3/6÷5/6 | | -4^-2*-80/-2*-4 | | 4(1-6x)=52 | | t+3.54=6.87 | | U^2+6u-29=0 | | y-3=2(x+3) | | 26=7m | | 5n-11=16 | | 2(v-5)-4=-5(-3v=2)-3v=-2/5 | | 3x+4=-0.35x-10 | | -3c+1=-3c | | 16=a/12 | | 5w^2-25w-120=0 | | 8z=9.5 | | 6t-rt=12fort | | 12-2b+5=-1 | | t(2t^2-t-10)=0 | | w/2=7.5/5=w/7.5=5/2 | | 5w-25w-120=0 | | -4x-26+2x+10=16+6x | | 7/9*54 | | 2x-(x-7x)=21 | | 7.3y-5.19=-51.9 |